Demographic, clinical and treatment characteristics of patients with Kaposi's sarcoma: A single-center study - SALMAN, ANDAÇ; ÖZGEN, ZÜLEYHA (MARMARA UNIV, FAC MEDICINE, 2019)
Objective: The clinical, demographic and treatment characheristics of patients with Kaposi's sarcoma (KS) are not well-detined. There is lack of consensus on treatment modalities. Thus, we aimed to define demographic, clinical characteristics and treatment outcomes in our cohort of patients with KS. Patients and Methods: A retrospective cohort study was done and all patients who were followed up in our specialized cutaneous tumors outpatient clinic with a diagnosis of KS between 2006 and 2018 were included in the study. Results: A total of 25 patients were included in the study. The mean age of the patients was 66 and 80% were male. The most common form of KS was classic type (80%). During a mean follow-up of 43 months, the most frequently administered treatments were cryotherapy, interferons, radiotherapy, topical imiquimod and topical timolol. Overall a complete response was observed in 9 (36%) patients. Conclusion: The clinical and demographic characteristics of our cohort match those observed in existing literature. We think that the use of local treatments such as cryotherapy, topical imiquimod should be used more frequently in patients with limited disease. Considering the efficacy of timolol in other vascular tumors, future prospective studies investigating the effects of timolol in KS are highly warranted.
Keywords: Cryotherapy; Kaposi's sarcoma; Timolol; Treatment